English-speaking Seniors Unite to Create Provincial Vote - Seniors Action Quebec (2013)

Commissioner's Findings Confirm Concerns of English-speaking Quebec - Quebec Community Groups Network (QCGN) (2013)

English-speaking Community Massively Opposed to Charter of Values - Quebec Community Groups Network (QCGN) (2013)

QCGN Launches Young Ambassadors Program to Encourage English-speaking Youth to Vote - Quebec Community Groups Network (QCGN) (2013)

QCGN Congratulates Shelly Glover New Minister for Canadian Heritage and Official Languages - Quebec Community Groups Network (QCGN) (2013)
Keywords: Official Language Minority Community (OLMC)

CRTC Must Oblige Vidéotron to Restore English-language Community Television Station - Quebec Community Groups Network (QCGN) (2013)

English-speaking Community Needs Formal Presence in Provincial Government, says QCGN members - Quebec Community Groups Network (QCGN) (2013)

CRTC Decision on CBC License Renewal Good News for English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2013)

QCGN Calls for Productive Dialogue with English-speaking Community - Quebec Community Groups Network (QCGN) (2013)

QCGN Opening Remarks to Committee on Culture and Education : General consultation and public hearings on Bill 14: An Act to Amend the Charter of the French Language, the Charter of Human Rights and Freedoms and Other Legislative Provisions - Quebec Community Groups Network (QCGN) (2013)

QCGN Approves New Roadmap for Canada's Official Languages - Quebec Community Groups Network (QCGN) (2013)

Federal Budget Indicates Government Comitted to Quebec's English-speaking Minority with a Renewed Roadmap for Official Languages - Quebec Community Groups Network (QCGN) (2013)

QCGN Leaders Disappointed by CAQ's Position on Bill 14 - Quebec Community Groups Network (QCGN) (2013)

Brief Presented to the National Assembly’s Committee on Culture and Education with Regards to General Consultation and Public Hearings on Bill 14: An Act to Amend the Charter of the French Language, the Charter of Human Rights and Freedoms and Other Legislative Provisions - Quebec Community Groups Network (QCGN) (2013)
This brief was prepared by the Quebec Community Groups Network (QCGN), an incorporated not-for-profit organization that identifies, explores and addresses strategic issues affecting the development and vitality of English-speaking Quebec. The QCGN and its 41 members work cooperatively and in partnership with community stakeholders, leaders, governments and institutions, to advance the interests of our minority community.

Mémoire présenté à la Commission de la culture et de l’éducation de l’Assemblée nationale en regard à la consultation générale et auditions publiques sur le projet de loi n°14, Loi modifiant la Charte de la langue française, la Charte des droits et libertés de la personne et d’autres dispositions législatives - Quebec Community Groups Network (QCGN) (2013)
Ce mémoire a été rédigé par le Quebec Community Groups Network (QCGN), un organisme à but non lucratif dont la mission est de cerner, de clarifier et de traiter les enjeux stratégiques qui affectent le développement durable et la vitalité du Québec d’expression anglaise. Le QCGN et ses 41 organismes membres travaillent ensemble et avec les intervenants communautaires, les leaders, les gouvernements et les institutions, pour faire valoir les intérêts de notre communauté en situation minoritaire.

QCGN Board of Directors : Resolution Regarding Bill 14, An Act to Amend the Charter of the French Language, the Charter of Human Rights and Freedoms and other Legislative Provisions, Tabled in the National Assembly of Quebec on December 5, 2012 - Quebec Community Groups Network (QCGN) (2013)